Working Ladies and Their Emotional Intelligence: Exploring the Relationship between Emotional Intelligence and Adjustment Problems in Working Women (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In the present study emotional intelligence of the ladies has been studied. In this study The sample of 714 women from ten textile industries in Coimbatore and Tiruppur Districts were selected with the help of Fishers Table of Random numbers. Tools used for data collection in this study were Adjustment Inventory. Emotional Quotient Inventory, Family Environment Scale by Bhatia, The data collected were statistically analyzed and the results of the study revealed that the adjustment problems of working women has significant relationship with their emotional intelligence, family environment, and self-concept. In addition, personal factors of working women influenced their adjustment problems. The findings of this study suggest that working women should consider the significance of emotional intelligence, family environment, and self-concept, while they are at home and in the working environment.